Nghiên cứu ảnh hưởng của bột khoáng sericit đến tính chất và quá trình chế tạo vật liệu cao su thiên nhiên - Thế, Ngô Kế (Vietnam Journal of Chemistry, 2014)
The using sericite mineral S1 and S2 are supplied by the laboratory on mineral materials of IMS. The effect of sericite on the compouding, processing and properties of cured natural rubber (NR) is demonstrated. The use of sericite as a filler for NR lowers the viscosity and therefore aids its compouding. The surface modified sericite by aminopropyltriethoxysilan accelerates curing process and reduces the time required to compoud products. The results indicate that sericite can be successful used in the manufacture of NR products. The cured NR with 20% of surface modified sericite S1 gives the best mechanical properties.